Molecular Identification of Isolated Fungi from Kelantan and Terengganu Using Internal Transcriber Spacer (ITS) Region - Noor Afiza, Badaluddin; Mohammad Hailmi, Sajili; Noor Asidah, Mohamed (2018)
Fungi are morphologically, ecologically, metabolically and phylogenetically diverse. Fungi play important roles as one of the major decomposer in ecosystems, dominated by Saprophytic fungi. The identification of fungi is important to differentiate each fungi owing to their special ability in our ecosystem. However, the identification of fungi is become very challenging for those untrained mycologists. Essentially, the identification of fungi at the species-level is more problematic. Traditional approaches, based on the morphological or physiological features alone are unreliable because of the limited amount of morphological characters for fungi identification. Thus, a reliable molecular approach is required to identify the fungi at species-level. Here, we have successfully identified the species of 25 isolated fungi samples from the polluted areas in Kelantan and Terengganu by using the molecular identification utilizing the Internal Transcribed Spacer (ITS) regions. Phylogenetics tree was then constructed, using MEGA v7.0 software to illustrate the inter-relationships among the isolates. Among of 25 isolated fungi samples, 23 were identified from Ascomycota division and another two were from the Zygomycota division. From our observation, the most frequent species grew for both polluted areas were from Lasiodiplodia sp.